Natural fruit set in Vanilla wightiana Lindl., an endangered species from Andhra Pradesh, India - Krishna Kumar, S N Potty, Y S Rao, K Mary Mathew, K J Madhusoodanan, M R Sudharshan, V (Journal of Spices and Aromatic Crops, 2000)
Vanilla wightiana Lindt, described as an extremely endangered wild species, occurs in the Eastern Ghat forest ranges of East Godavari District of Andhra Pradesh, India.